2016
DOI: 10.1101/063404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abstract spatial, but not body-related, visual information guides bimanual coordination

Abstract: Visual spatial information is paramount in guiding bimanual coordination, but anatomical factors, too, modulate performance in bimanual tasks. Vision conveys not only abstract spatial information, but also informs about body-related aspects such as posture. Here, we asked whether, accordingly, visual information induces body-related, or merely abstract, perceptual-spatial constraints in bimanual movement guidance. Human participants made rhythmic, symmetrical and parallel, bimanual index finger movements with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Bingham et al, 2018). Qualitatively, this measure renders similar results as the phase difference (Brandes et al, 2017), but we report it in the Supplementary Information to aid comparison with earlier work.…”
Section: Methodsmentioning
confidence: 78%
See 3 more Smart Citations
“…Bingham et al, 2018). Qualitatively, this measure renders similar results as the phase difference (Brandes et al, 2017), but we report it in the Supplementary Information to aid comparison with earlier work.…”
Section: Methodsmentioning
confidence: 78%
“…However, later studies also demonstrated a role of perceptual factors (Brandes, Rezvani, & Heed, 2016;Heed & Röder, 2014;Oliveira & Ivry, 2008;Swinnen et al, 1998;Temprado, Swinnen, Carson, Tourment, & Laurent, 2003; for review, see Shea, Buchanan, & Kennedy, 2016). For instance, when the index fingers are wiggled with one hand turned up, and the other down, symmetrical movements are still performed more successfully than parallel ones, although they now require concurrent activation of non-homologous muscles (Brandes et al, 2017;Heed & Röder, 2014;Mechsner et al, 2001).…”
Section: Bimanual Coordinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Amazeen, DaSilva, & Amazeen, 2008;Meesen, Wenderoth, Temprado, Summers, & Swinnen, 2006;Salesse, Temprado, & Swinnen, 2005;Wilson, Collins, & Bingham, 2005a, 2005b, homology tends to show larger effect sizes and can often dominate (e.g. Kagerer, Summers, & Semjen, 2003;Li, Levin, Forner-Cordero, Ronsse & Swinnen, 2008;Peper, de Boer, de Poel, & Beek, 2008;Temprado, Swinnen, Carson, Tourment & Laurent, 2003;although see Meschner, Kerzel, Knoblich &Prinz, 2001, andBrandes, Rezvani, &Heed, 2017, for examples of allocentric dominance).…”
Section: Egocentric Vs Allocentric Constraintsmentioning
confidence: 99%